HUBUNGAN ANTARA KEMAMPUAN MENGAJAR GURU DAN KOMUNIKASI INTERAKTIF DENGAN HASIL BELAJAR BAHASA INDONESIA SISWA SMA NEGERI 1 RANTAU SELATAN - Annim Hasibuan (MEDAN MAKNA: Jurnal Ilmu Kebahasaan dan Kesastraan, 2019)
This quantitative study aimed to determine the relationship between (1) the ability of teachers to teach Indonesian learning outcomes, (2) interactive communication and learning outcomes Indonesian, and (3) the ability of teachers to teach and interactive communications Indonesian learning outcomes. The study population was all students SMA South Rantau District Labuhanbatu the number of 242 students sample 40 randomly selected students based on class and two teachers. Variable data in this research is quantitative data in the form of teachers' teaching ability scores (X1), a score of interactive communication (X2), and a score of Indonesian learning outcomes (Y). Based on the results of multiple linear regression analysis and partial correlation showed a positive relationship between teachers' teaching ability and interactive communication with the Indonesian learning outcomes. It is seen from (1) multiple regression equation = -54.59 + 0.75 X1 + X2 0:53 linear, (2) the coefficients a1 and a2 significantly positive effect and multiple linear correlation coefficient = 0.94 is significant Ry12 with a contribution of 92%. Partially there is a positive relationship between the ability of teachers to teach Indonesian learning outcomes and there is a positive relationship between interactive communication with the Indonesian learning outcomes.